2021
DOI: 10.1167/iovs.62.6.18
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Transcriptional and Chromatin Accessibility Heterogeneity of Proliferating Cone Precursors in Human Retinoblastoma Tumors by Single Cell Sequencing—Opening Pathways to New Therapeutic Strategies?

Abstract: Dissecting the transcriptional and chromatin accessibility heterogeneity of proliferating cone precursors in human retinoblastoma tumors by single cell sequencing-opening pathways to new therapeutic strategies?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…Cone precursors and retinoblastoma cells, two major cell types with different transcriptomic profiles, were identified in retinoblastoma. Coincidentally, in 2021, Collin et al also used single-cell sequencing to verify that G2/M cone precursors subset was the cell of origin for retinoblastoma [ 30 ]. This was consistent with our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cone precursors and retinoblastoma cells, two major cell types with different transcriptomic profiles, were identified in retinoblastoma. Coincidentally, in 2021, Collin et al also used single-cell sequencing to verify that G2/M cone precursors subset was the cell of origin for retinoblastoma [ 30 ]. This was consistent with our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, attempts also have been made to understand cellular heterogeneity and origins of RB using scRNA-seq. Collin et al [ 22 ] revealed G2/M cone precursors as the cell of origin in RB. Yang et al [ 23 ] revealed that the RB cells originated from the cell cycle-assoicated cone precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Among those, 4 clusters expressing cone and proliferation markers were selected for further analysis as follows: (1) proliferating cone precursors (cluster 1) composed of cells in S and G2/M phase of the cell cycle ( Fig. 4B ) and characterized by high expression of cone precursors ( DCT , PDE6H , AIPL1 , TULP1 , RXRγ ), proliferation markers ( HIST1H4C , TOP2A, MKi67 , PCNA , MCM3 , CDC25A , CDC25C , CHEK1 , E2F3 , PRC1 , SKP2 , UBE2C ), and DEK , KIF14 , MYCN , SYK (characteristic for Rb) which was defined as Rb-like cluster 21 , 22 , 42 , 49 , 50 ( Fig. S7A ); (2) cluster 8 , characterized by high expression of cone precursor markers ( PDE6H , GNB3 , RXRγ , ARR3 , GNGT2 ), retinoma marker ( CDCA7 , HELLS ), and PCNA proliferation marker, but greatly reduced expression of MKi67 , which was defined as retinoma-like cluster 9 , 42 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S8D ). Recently, our group has published single-cell RNA-Seq of human Rb tumors, 49 which were further assessed for marker co-expression indicated above. This analysis indicated co-expression of RXRγ with Ki67 and GAP43 or ONECUT1 in G2/M cone precursors clusters 8 and 12 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation